Forms of Discrimination on Subalternity Group in Navis’s Saraswati : Si Gadis Dalam Sunyi Shortstory - Dina Fauzana; Sulastri Sulastri; Zurmailis Zurmailis (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2020)
This research is motivated by the colonial problem in the archipelago which still leaves a trail of oppression as well as the struggle of the natives to escape the impact of this ideology. The colonial trail that still lags behind creates an indigenous group that becomes a subaltern - an isolated, oppressed, and exiled group. In the postal colonial subaltern theory Gayatri Spivax stated that among the groups that were the most victims of colonialism were the subalterns. Relevant to the problem, this study aims to describe the forms of discrimination against subaltern groups, especially women who become subaltern groups, against colonial ideology. Data obtained from Saraswati : Gadis dalam Sunyi shortstory by A. A Navis that is analyzed qualitatively. Based on research data sources namely Saraswati : Gadis dalam Sunyi shortstory by A. A Navis. The results of this study indicate that the figure Saraswati became subaltern because she is marginalized, economically impoverished, labeled, and sexually abused.